Change of Mg concentration in several plants depending on plant species, washing status, and traffic density - Ozel, Halil Baris; Varol, Hande Nur; Sevik, Hakan (GSC Online Press, 2021)
Air pollution is one of the most important problems threatening the organic life and ecosystem throughout the world. Among the components of air pollution, the most important ones are the heavy metals that can be toxic and carcinogenic even at low concentrations and even the nutrient elements can be harmful when at high concentrations. Thus, monitoring the heavy metal pollution in the air is very important and plants are widely used as biomonitor for this purpose. However, which plants and organs are more suitable for monitoring which heavy metal pollution can be determined with detailed studies. In the present study, it was aimed to determine which plant species and which organ of that species would be more suitable for monitoring the concentration of magnesium (Mg) in air. For this purpose, five organs of five species grown in regions having different traffic densities were examined. In conclusion, it was found that Mg concentration in washed bark of Robinia pseudoacacia, wood of Platanus orientalis, washed leaves of Ulmus minor, and non-washed leaves of Acer negundo and Nerium olender increased with increasing traffic density.
Keywords: Air pollution; Heavy metal; Biomonitor; Magnesium; Mg; 13. Climate action; 15. Life on land; 6. Clean water; 12. Responsible consumption